Utilization of Ginger Powder (Zingiber officinale) as Larvicide for Aedes Aegypti - Alkausyari Aziz; Khayan; Slamet Wardoyo (Gema Lingkungan Kesehatan, 2024)
Aedes aegypti mosquitoes are known vectors for Dengue Fever (DF). This disease is caused by the Dengue virus, necessitating control measures that do not harm public health. One such measure is the use of ginger powder (Zingiber officinale) as a larvicide against Aedes aegypti larvae, the vector of DF. This experimental study employed a Completely Randomized Design with statistical analysis using the F-test. Four treatment concentrations and one control were tested: 5 grams, 10 grams, 15 grams, and 20 grams, with three repetitions for each treatment, observed over a 4-hour period. The study aimed to determine the effect of ginger powder (Zingiber officinale) as a larvicide on Aedes aegypti larvae. The average larval mortality at a concentration of 5 grams was 4.3 larvae, 7.6 larvae at 10 grams, and 10 larvae at both 15 grams and 20 grams. The F-test results showed that at the 1% level, Fht > Ftb. Duncan's Multiple Range Test indicated that the effective concentration was 15 grams, at which all Aedes aegypti larvae died within 4 hours. The utilization of ginger powder (Zingiber officinale) as a larvicide, with varying amounts of powder, resulted in different larval mortality rates. The higher the concentration of ginger powder (Zingiber officinale), the higher the larval mortality rate of Aedes aegypti.